The Berlin plans of Kamianets-Podilskyi - OPYRCHAŁ, Leszek; OPYRCHAŁ, Urszula; NAHNYBIDA, Ruslan (Historia i Świat, 2021)
The article discusses five manuscript plans of Kamianets-Podilskyi which are present in Berlin. Four of them are available in the collections of the Staatsbibliothek zu Berlin (The Berlin State Library) and one – at the Geheimes Staatsarchiv Preußischer Kulturbesits (Secret State Archive of Prussian Cultural Heritage). Despite the fact that the list of maps and plans of areas present in the former socialist countries in Europe was published in 1976, these plans remained unknown to both, Polish and Ukrainian researchers analysing the history of fortification. Three of the discussed four plans are especially important. The first one is the plan by Christian Dahlke, an engineer who fortified Kamianets-Podilskyi, the later commanding officer of this fortress. The second one is an anonymous plan from 1740, most probably created during the inspection of the fortress reinforcements which was carried out by Saxon engineers. The third one is the plan by G. de Hundt. Identical versions of this plan are located in Cracow, in Vienna and in Moscow. Due to the fact that both, Austria as well as Russia, conducted military activities in Podolia in the 18th century, nearly identical plans of the Kamianets-Podilskyi Fortress, present in the capitals of those countries, indicate that G. de Hundt worked not only for the Polish king, but also for foreign intelligences.